Carbon-Oxygen Hydrogen Bonding in Biological Structure and Function - Horowitz, Scott (American Society for Biochemistry and Molecular Biology, 2012)
Carbon-oxygen (CH···O) hydrogen bonding represents an unusual category of molecular interactions first documented in biological structures over 4 decades ago. Although CH···O hydrogen bonding has remained generally underappreciated in the biochemical literature, studies over the last 15 years have begun to yield direct evidence of these interactions in biological systems. In this minireview, we provide a historical context of biological CH···O hydrogen bonding and summarize some major advancements from experimental studies over the past several years that have elucidated the importance, prevalence, and functions of these interactions. In particular, we examine the impact of CH···O bonds on protein and nucleic acid structure, molecular recognition, and enzyme catalysis and conclude by exploring overarching themes and unresolved questions regarding unconventional interactions in biomolecular structure.